AKTIVITAS PENYEMBUHAN LUKA BAKAR FRAKSI EKSTRAK ETANOL 96% DAUN COCOR BEBEK (Kalanchoe pinnata) [Lam.] Pers. - Ratu Zahra, Elisia Herma; WS, sri Harsodjo; maifitrianti, maifitrianti (Universitas Muhammadiyah Prof. DR. HAMKA, 2017)
Kalanchoe pinnata leaves was used  as an alternative medicine by the people of Indonesia, such as burned wound healing. This research was done to determine whether the three fractions (fraction polar, semi-polar and non-polar) has a healing activity burns on white male rats 25 male rats was divided into five groups positive control (Bioplacenton®), negative control (Base Gel) and three groups of variations of the fraction (fraction polar, semi-polar and non-polar fraction. The backs of rats induced hot metal with a temperature of 100oC and with a diameter 2x2 cm for 30 seconds. Observations diameter wound was observed on days 3,6,9,12 and 15 with the parameters of diameter reduction burns and days where faster wound shut. Polar fraction Kalanchoe pinnata with a dose of 1,29%, semi-polar fraction of 0,05% and 0,03% non-polar fractions in a gel formulation has a burned wound healing activity starting from day 12.